Frontier Landscapes: Christian Conquests and Agrarian Transformations from the Twelfth to the Fourteenth Century (Edad Media. Revista de Historia, 2019)
In this article, a conceptual framework is provided for the analysis of the agrarian expansion of the European feudal system in the ‘outlying’ territories annexed through military conquest. The most adequate category with which to conceptually frame these processes is understood to be the frontera (frontier), understood as the geographical movement that expands the pillage of the cabalgadas (quick-striking raids) with the seizing of land booty, or ‘cheap nature.’ The Iberian case is briefly reassessed in this light by taking recourse to the three pillars in any historical analysis of this issue: population movements (colonial immigration and the displacement of native populations); ‘spatialisation’ as the physical materialisation of the imposition of seigneurial relationships (concentrated habitats, regularisation of land plots); and land reclamation, the last step in the colonisation of captured ecosystems.
Keywords: Conquest; Frontier; Migrations; Land distribution; Land reclamation